Language Errors in Culinary Culture Differences of Intermediate Level BIPA Students at Universitas Brawijaya - Teddy Afriansyah; Shonia Rahma Putri; Salma Reza Adinda; Kharisma Shinta; Clementina Vincencia Kandam; Dany Ardhian (Jurnal Budaya, 2024)
The use of information and communication technology in learning Indonesian for Foreign Speakers (BIPA) at Universitas Brawijaya created a trend of popularity in the use of culinary vlog videos by middle-level students. Despite making a positive contribution, the use of this technology often leads to morphosemantic errors in the use of Indonesian. These errors include aspects of word use, sentence structure, and vocabulary selection that do not conform to language norms. This study used a qualitative descriptive approach by observing three culinary vlog videos as samples. The method in collecting data, this research employs observation and note-taking techniques. Subsequently, data analysis is conducted through three stages, namely the first stage involves data reduction to simplify information, the second stage focuses on presenting data for better clarity, and the third stage entails formulating conclusions based on the results of the conducted analysis. The results of the study found that there were 9 morphosemantic error data in the first video with Olivia, 4 morphosemantic error data in the second video with Lestari, and 5 morphosemantic error data in the third video with Dalia. It can be concluded that language errors that arise can affect the understanding and clarity of messages conveyed in daily communication. With a better understanding of language errors, it is expected to contribute to maintaining the quality of good and correct use of Indonesian in various daily communication situations. Keywords: language errors, culinary culture, BIPA students